2017
DOI: 10.1088/1752-7163/aa61c5
|View full text |Cite
|
Sign up to set email alerts
|

Serum and exhaled breath condensate leptin levels in asthmatic and obesity children: a pilot study

Abstract: This study shows that leptin is measurable in EBC in children and that EBC-leptin levels are significantly higher in the obese subjects and in asthmatic ones compared with healthy subjects. Leptin may therefore represent a non-invasive marker of non-specific airway inflammation in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…In the case of children, Guler et al [93] also found a positive relationship between asthma and leptin serum levels. Bodini et al [94] measured the level of leptin in serum and exhaled breath condensate (EBC) in 61 asthmatic and non-asthmatic children from 6 to 14 years old. Those authors also considered the obese and non-obese status based on the BMI.…”
Section: Pro-inflammatory Adipokines: Leptin and Resistinmentioning
confidence: 99%
“…In the case of children, Guler et al [93] also found a positive relationship between asthma and leptin serum levels. Bodini et al [94] measured the level of leptin in serum and exhaled breath condensate (EBC) in 61 asthmatic and non-asthmatic children from 6 to 14 years old. Those authors also considered the obese and non-obese status based on the BMI.…”
Section: Pro-inflammatory Adipokines: Leptin and Resistinmentioning
confidence: 99%
“…Besides, leptin can promote the production of leukotrienes, increase the secretion of immune factor immunoglobulin E, and elevate the expression of inflammatory mediators, thus leading to airway inflammatory response. 20 The shortcoming of this study was that our preliminary data should be further validated with a large number of samples and the exact mechanism pathway of adiponectin and leptin to exacerbate the asthma has not been determined, and it will be the emphasis in subsequent research.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical researches also showed that the levels of leptin in EBC from asthmatic children were significantly higher than normal children. 30 On the other hand, adiponectin, another important adipokine produced by adipocytes, is significantly decreased in obese subjects. Conversely, weight loss promotes an increase on adiponectin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Newson and colleagues 12 found that leptin and leptin/adiponectin ratio were positively associated with the severity of asthma according to a clinical follow-up survey. Besides, through evaluating the levels of leptin in exhaled breath condensate (EBC) from asthmatics, normal and overweight children, Bodini et al 13 found that EBC-leptin levels are significantly higher in the obese subjects and in asthmatic ones compared with healthy subjects. Therefore, leptin might translocate to the airway and play a role on the airway inflammation.…”
Section: Introductionmentioning
confidence: 99%